Imatinib-induced Ototoxicity in a Patient with Gastrointestinal Stromal Tumor (GIST) - Wasif, Komal (Cureus, 2016)
Imatinib (Gleevec) is a biological agent that is approved for the treatment of chronic myeloid leukemia (CML) as well as gastrointestinal stromal tumor (GIST). The most frequently seen adverse effects in patients treated with imatinib include superficial edema, muscle cramps, musculoskeletal pain, rash, fatigue, headache, abdominal pain, and joint pain. Ototoxicity has rarely been reported except in two cases. We report a case of bilateral irreversible sensorineural hearing loss (SNHL) caused by imatinib in a patient receiving this agent in the adjuvant setting. This case underlines the importance of early recognition of this potential toxicity that can impact the quality of life.